Peran Badan Permusyawaratan Desa (BPD) dalam Penyelenggaraan Pemerintahan di Desa Massenrengpulu Kecamatan Lamuru Kabupaten Bone - Sakir, Ahmad Rosandi; Almahdali, Humairah (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2024)
This study aims to analyze the role of the Village Consultative Body (Badan Permusyawaratan Desa or BPD) in the governance of Massenrengpulu Village, Lamuru Subdistrict, Bone Regency, as well as the influencing factors. To achieve this objective, the research employs a qualitative method with a descriptive approach to data collection. Observation, interviews, and analysis of documents and archives are utilized to gather the necessary data. The findings of the study indicate several key points. Firstly, in analyzing the BPD's role in the governance of Massenrengpulu Village, Lamuru Subdistrict, Bone Regency, the BPD is actively involved in discussing and agreeing on the draft village regulations with the village head. Ongoing coordination between the village government and the BPD ensures the smooth process of discussing and crafting village regulations. Secondly, the role of the BPD as a receptacle for community aspirations has been fulfilled as expected. The BPD has effectively served as a platform to receive and channel community aspirations related to village development. The BPD's proactive involvement in internal meetings and coordination with the village government demonstrates the smoothness of the process, in line with the intended objectives